2009
DOI: 10.1159/000256658
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Low Glucose Degradation Product Bicarbonate/Lactate-Buffered Dialysis Solution on the Epithelial-Mesenchymal Transition of Peritoneum

Abstract: Background: Epithelial-mesenchymal transition (EMT) is important in the development of peritoneal fibrosis. Glucose degradation products (GDPs) may induce EMT in human peritoneal mesothelial cells (HPMCs). Methods: The effects of individual GDPs and GDPs derived from peritoneal dialysis fluid (PDF) in both HPMCs and peritoneal membranes were evaluated. EMT was assessed with α-smooth muscle actin (α-SMA) and E-cadherin. Results: In vitro, α-SMA protein and mRNA levels increased in the presence of the GDPs (form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…In agreement with our results, a recent report showed that various GDPs present in standard PD fluids can induce EMT of MCs in vitro and that low-GDP fluids have less impact on peritoneal fibrosis and EMT in vivo in a rat model (27). All of those results accord with results obtained in several patient series, including the present report (16,17).…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with our results, a recent report showed that various GDPs present in standard PD fluids can induce EMT of MCs in vitro and that low-GDP fluids have less impact on peritoneal fibrosis and EMT in vivo in a rat model (27). All of those results accord with results obtained in several patient series, including the present report (16,17).…”
Section: Discussionsupporting
confidence: 94%
“…Glucose degradation products (GDPs), such as methylglyoxal (MGO) and glyoxal, are generated from the degradation of glucose during heat sterilization and storage [3]. MGO is an extremely toxic GDP that may cause peritoneal injury during the epithelial-mesenchymal transition (EMT) of peritoneal mesothelial cells (PMC) [4,5]. EMT is a dynamic process in which epithelial cells undergo a phenotypic conversion that gives rise to a fibroblastoid appearance.…”
Section: Introductionmentioning
confidence: 99%
“…Often, GDP are generated as a consequence of heat sterilizing peritoneal dialysis (PD) fluids. GDP triggers the formation of advanced glycation end-products in the peritoneal cavity, as well as producing extensive cytotoxicity and cell transformation by means of a poorly understood mechanism (Witowski and Jörres, 2000; Schwenger, 2005; Oh et al, 2010; Pischetsrieder and Gensberger, 2012). …”
Section: Discussionmentioning
confidence: 99%